Netflix English subtitling of the Jordanian movie ‘The Alleys’: Challenges and strategies - Saideen, Bassam; Thalji , Abdullah; Lababaneh, Abdulkareem; Tartory , Raeda; Haider, Ahmad S; Obeidat, Mohammed (Research Journal in Advanced Humanities, 2024)
This study examined the translation strategies employed in subtitling the Jordanian Movie The Alleys from Jordanian vernacular into English, with special attention to culture-specific items (CSIs) and swear words. The selected movie was produced in 2022 and aired on Netflix. After watching the movie and examining the subtitles, the researchers grouped them into two main categories: culture-specific items (CSIs) and Swear Words. The themes subcategorized under CSIs include i) idioms and proverbs, ii) terms of address, iii) religious expressions, iv) oaths, and v) food and drinks. The themes identified in the movie and subcategorized under Swear Words include i) relative-related, ii) sex-related, iii) animal-related, iv) excretion, and v) rudeness and disrespect. The study utilized the translation strategies proposed by Baker (2001), Gottlieb (1992), and Mughazy (2016). The findings showed that the strategies used in translating idioms and proverbs are metaphorical approximation (idiom to idiom), metaphorization, and literalization (paraphrase). The strategies used in rendering terms of address, religious expressions, food & drinks are cultural adaptation, deletion, substitution, and generalization. Swear words were translated using various strategies: substitution, addition, deletion, or literal translation. The study concluded that language could be creatively and strategically altered to capture cultural contexts, feelings, and underlying meanings. These translation choices might not be merely linguistic tweaks but calculated efforts to accurately capture the essence of the original expressions with clarity and emotional resonance in the target language.